Translation Problems Analysis and Application of the Grammar-Translation Method in EFL Class - Pornchai Pornwiriyakit; Warinthon Dandee (Journal of Educational Issues, 2024)
This research aims to study the problems of translating word and sentence structures from English into Thai made by students and to solve the English-to-Thai translation problems occurred in the paper test. The samples consisted of 127 students majoring in English for International Communication at Rajamangala University of Technology Tawan-Ok. The research instrument was an English-to-Thai translation test covering grammatical and lexical aspects. The collected data were analyzed by using descriptive statistics with frequencies, percentage, mean, standard deviation and interferential statistics. The data were analyzed and compared the differences of scores obtained from the pretest and the posttest with a confidence interval at 0.05. The results showed that the samples made more mistakes of grammatical aspect than the lexical aspect before the experiment. The grammatical aspect was at the low level representing 16.38% while the lexical aspect showed 70.30%. After applying the grammar-translation method into the samples, the posttest results showed the better scores on English grammatical structures at 78.8% while the lexical knowledge at 97.53%. It is clear that the grammar-translation method made less translation problems.